Exchange rate re-examined: The varying impact of import and export on exchange rate volatility - Azimi, Mohammad Naim (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
This paper examines the varying impact of the Import and Export on the impulsiveness nature of the Exchange Rate in four EU (European Union) economies such as Austria, Germany, France and Italy for a period of 56 years from 1960 – 2015. In achieving an accurate result for testing this competing null hypothesis, variables are pooled by regression and the computation of random effects model is found to be rational upon which, the ultimate conclusion is drawn. The statistical results obtained from random effects model show that export is not a significant variable to impact the exchange rate while the import is found to be significant to impact the impulsiveness of the exchange rate across the economies over the concerned period of time. The validity and non-existence of cross sectional independence is further documented by statistical results obtained from the Hausman test.